DEVELOPING ENGLISH INSTRUCTIONAL MATERIALS FOR STUDENTS OFCOMPUTER SCIENCE DEPARTMENT (A NEEDS ANALYSIS) - Fransisca Endang Lestariningsih; Arida Susyetina; Lucia Dwi Krisnawati (Universitas Ahmad Dahlan)
English is one of compulsory subjects at the computer science department in a higher education. Since English is not a field of study at the computer science, it is taught as an ESP (English for Specific Purposes). The fact that English is part of the curriculum at the computer science department makes it challenging for both the teachers and the students. The majority of the students will always deal with motivation, whereas teachers face a great challenge in designing an appropriate instructional material that gives short-term and long-term effects to the students. Besides, there are two types of teachers who teach English for computer science students, English teachers who have English education background and English teachers who do not own degrees in English education. These two types of teachers experience their own strengths and weaknesses in designing English instructional materials. This research, therefore, will combine the strengths of the teachers in the development of English instructional materials for computer science students that will have short-term and long-term impacts to the students. This research is applying an action research which is divided into some cycles of planning, action, observation, and reflection. The participants are three English teachers and two classes of computer science students.